Issues of Developing the Socio-Philosophical Foundations of the Educational Space - Yu. Zhang; S. N. Tsaplin; I. V. Yakovleva (Дискурс)
Introduction. In fact, any ideological or methodological construction represents a certain system of knowledge, including initial concepts, rules for constructing statements and conclusions of derivative judgments, which, after the necessary discussion and confirmation, take the form of a universal belief. The methodology for developing unified prolegomena in the description of the modern educational space, stated in world socio-political philosophy and in the philosophy of education, meets similar criteria. This need requires clarifying how and in what way, with the help of rational philosophical thought, it is possible and necessary to develop a methodology that unites the categorical apparatus of numerous educational systems.Methodology and sources. The description of the unified categorical foundations of the educational space is carried out in the ontological, epistemological and axiological content of the priorities represented by the modern educational space.Results and discussion. The methodology of globalism in social philosophy and in the philosophy of education is theoretically organized and hierarchized. In general, it includes the interests and needs, meanings and values of the subjects of knowledge. The discovery of fundamental guidelines in the ontological, epistemological and axiological priorities of philosophical and educational discourse in matters of building a global educational space necessitates a critical philosophical assessment of globalization theoretical and methodological approaches from the point of view of the socio-noospheric methodology of cognition. This is important when developing unified categorical frameworks for describing the educational space.Conclusion. The methodological potential of the philosophy of education as a humanistic basis for the development of humankind has high heuristic significance in the aspect of the dialectics of the media space with the possibilities of education integrated into it. A single categorical space, framed in the methodology of ontology, epistemology and axiology of education, in practical implementation is capable of being projected into the mass world perception and worldview, based on the in-depth development of the socio-noospheric methodology of the educational space.